2014
DOI: 10.1080/19443994.2013.848652
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of high-concentration ammonia in groundwater by a naturally formed co-oxide filter film

Abstract: A B S T R A C TOperation of a sand filter system in treating groundwater produces a high concentration of ammonia (2-2.8 mg L À1 ), iron (0.9-2 mg L À1 ) and manganese (1.2-1.7 mg L À1 ), and on the surfaces of quartz sands, a co-oxide filter film is formed. The removal of ammonia in the filter before and after the treatment of film-coated sands at high temperature and pressure and the transformation of nitrogen in filter bed were studied. The morphology and chemical composition of film-coated sands were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The results showed that the specific surface area increased from 0.106 m 2 /g (virgin sand) to 3.920 m 2 /g (filter media collected on 12th day). Cao et al reported that the increased specific surface area provided more active sites for NH 4 + -N catalytic oxidation, which played a decisive role in the catalytic oxidation process of NH 4 + -N [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the specific surface area increased from 0.106 m 2 /g (virgin sand) to 3.920 m 2 /g (filter media collected on 12th day). Cao et al reported that the increased specific surface area provided more active sites for NH 4 + -N catalytic oxidation, which played a decisive role in the catalytic oxidation process of NH 4 + -N [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chemical catalytic oxidation of ammonium by MeO x has been proven in groundwater [ 11 , 29 ]. The study of Guo et al indicated that microorganisms may play a negligible role in the process of ammonium removal by MeO x in groundwater [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…10 High ammonium concentrations in groundwater are difficult to handle because of limitation of inadequate dissolve oxygen (DO). 11 Some ammonium treatment methods have been developed such as steam stripping in packed columns to volatilize free ammonia, 12 using catalytic oxidation, 13,14 aeration combined with a chemical catalytic oxidation filter, 11 biological aerated filter, 15 and ion exchange onto clinoptilolite. 16 Although these methods have their own advantages and disadvantages, they are not easy to apply for ammonium removal from groundwater for suburban and rural communities in Viet Nam, where are lack of centralized supply water treatment plants.…”
Section: Ammonium (Nhmentioning
confidence: 99%